Temporal and geographic analyses of colorectal cancer screening during and after the COVID-19 pandemic in a federally qualified health center - Gloria D. Coronado; John F. Dickerson; Ming-Hsiang Tsou; Namrata Shivaprakash; Ana G. Rosales; Jackson L. Voelkel; Meisha A. Whyte; Elizabeth Shuster; Amanda F. Petrik; Josheili Y. Llavona-Ortiz; Charisma L. Jenkins; Carolyn M. Rutter; et al. (PLoS ONE, 2026)
Background The COVID-19 pandemic caused reductions in cancer screening services. We assessed the pandemic’s impact on colorectal cancer screening in a large diverse federally qualified health center (FQHC) in Los Angeles, CA. Methods We used interrupted time series regression to estimate trends in monthly colorectal cancer screening rates for four relevant COVID-19 pandemic periods: pre-pandemic (March 2018 – February 2020); early-pandemic (March – December 2020); vaccine-era (January 2021– May 2023); and post-pandemic (June 2023 – May 2024). We plotted spatial distribution patterns of screening across census tracts. Results Participants were 83,430 unique individuals (55% male; 80% Hispanic) ages 50–75. Average monthly colorectal cancer screening rates dropped from 9.3% pre-pandemic to 5.9% early-pandemic. Monthly screening rates in the vaccine era (7.5%) never returned to pre-pandemic levels and further declined in the post-pandemic era (6.7%; p trend = 0.09). Screening rates were consistently higher for males, ages 65–75, Hispanic individuals, and Spanish-preferring individuals in both pre-COVID (March 2018-Feb 2020) and post-COVID (July 2020-May 2024) periods. Increases in stool-based testing aligned with mailed outreach campaigns. Conclusions Monthly post-pandemic screening rates never reached pre-pandemic levels and declined from 2023 to 2024. Sharp increases in stool-based testing coincided with mailed outreach events, highlighting the importance of home-based screening methods during disruptive events. Impact Our findings can help shape healthcare response strategies to reduce screening delays in the context of future natural disasters.